Pragmatic Management of Hand Involvement in Extended Oligoarticular Juvenile Idiopathic Arthritis: Ultrasound-guided Serial Interphalangeal Joint Injections - İsa Cüce; Rıdvan Yıldızhan; Enes Veziroğlu; Ayşenur Paç Kısaarslan (Galenos Publishing House, 2023)
Small-joint involvement, including the interphalangeal joints of the hand, is less common in oligoarticular juvenile idiopathic arthritis (JIA). Ultrasound (US)-guided joint injections are also plausible for children. However, US-guided injections into pediatric small joints make the tips and tricks special because of the more difficult injection technique and greater risk of potential complications than with large joints. Here, we report the tips and tricks of serial US-guided interphalangeal joint injections in a male child with oligoarticular JIA who progressed to extended polyarthritis after an initial 6-month follow-up.